2021
DOI: 10.1021/acsami.1c13840
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Stretchable Triboelectric Nanogenerators Improved by Postcharging Electrode Material

Abstract: Sustainable ultrathin stretchable power sources have emerged with the development of wearable electronics. They obtain energy from living organisms and the environment to drive these wearable electronics. Here, an ultrathin stretchable and triboelectric nanogenerator (TENG) improved by chargeable carbon black (CB)/thermoplastic polyurethane (TPU) composite material (CT-TENG) is proposed for mechanical energy harvesting and physiological signal sensing. The CB/TPU composite can act as both a stretchable electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…This system which possessed a denser interlinked network of CB fillers is also a good example of the ability of flexible thermoplastic elastomers to accommodate a considerable amount of filler without affecting their flexibility. 26 In all these cases, it can be observed that the stretchability comes from the polymeric domain and does not interfere with the conductive pathways provided by the other component. The major factor to be considered in obtaining excellent surface charge density and power output for TENGs used in wearable application is to render the electrode material highly conductive.…”
Section: General Requirements Of Stretchable Components In Wearable T...mentioning
confidence: 93%
“…This system which possessed a denser interlinked network of CB fillers is also a good example of the ability of flexible thermoplastic elastomers to accommodate a considerable amount of filler without affecting their flexibility. 26 In all these cases, it can be observed that the stretchability comes from the polymeric domain and does not interfere with the conductive pathways provided by the other component. The major factor to be considered in obtaining excellent surface charge density and power output for TENGs used in wearable application is to render the electrode material highly conductive.…”
Section: General Requirements Of Stretchable Components In Wearable T...mentioning
confidence: 93%
“…TENG is known to convert the distributed mechanical energy into electricity by coupling electrostatic induction and triboelectrification. [50][51][52] This kind of flexible device works based on mechanical deformations under the external stimulus, thus electrode reliability of the device under deformations is one of the important factors to affect triboelectric output. Herein, we designed an Ag NWs-based single-electrode TENG based on the MPVA/Ag NPs fiber membrane to study its resistance response as well as triboelectric stability.…”
Section: Electrical Response Of the Mpva/ag Nps Fiber Membrane Based ...mentioning
confidence: 99%
“…Stretchable and/or shape adaptable 41 [53,79,126,130,158, Ultrathin d) 5 [183,190,205,210,213] Transparent 9 [130,158,182,187,194,196,203,206,213] Sweat permeable 1 [213] Wireless connected 5 [208,[214][215][216][217] Low-cost 11 [179,183,188,190,191,198,199,204,211,214,218] Facile manufacturing 6 [179,183,184,188,199,214] Biocompatible 4 [53,79,190,213] Metal-free 1 [219] Humidity resistive 2 [181,220] Self-healable 5…”
Section: Hmimentioning
confidence: 99%